Empower! To Win: An Action Guide to the Imperative Leadership Style of the 21st Century - Brady, Gene F. (Xlibris Corp., 2009)
Keywords: Leadership; dept.mgt

The lobster tale: an exercise in critical thinking. - Stepanovich, Paul L (Journal of Management Education, 2009)
Professors in management and business are encouraged to incorporate critical thinking as an objective in their courses. "The Lobster Tale" provides an opportunity to engage students in various levels of critical thinking, ranging from a relatively superficial reading to an examination of the deeper, often hidden issues. Using the foundations of critical theory and systems theory, the story draws on economics, social theory, philosophy, and other disciplines to present a simplified version of the complexities found in our global environment. It can be used to supplement a variety of courses in the business curriculum and to encourage students to challenge not only assumptions but also conventional wisdom and, perhaps, knowledge itself. © 2009 The Author(s).
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-736-247-110-079 tex.type: [object Object]
Keywords: Affirmative action; Critical theory; Critical thinking; Systems theory; Tragedy of the commons; dept.mgt